A Single Base Pair Deletion in the Promoter Region of the Factor IX Gene Is Associated with Haemophilia B - Hall, Adrian J; Chuansumrit, Ampaiwan; Peake, Ian R; Winship, Peter R (Thrombosis and Haemostasis, 1994)
Patients with the haemophilia B Leyden phenotype show a distinct pattern of factor IX expression characterized by a post-pubertal increase in FIX levels and the remission of clinical symptoms in adult life. This phenotype has previously been linked to single base mutations within transcription factor binding sites in a region of ∼40 bp around the major start point of transcription of the FIX gene. Here we report a novel mutation in this region within the transcription factor C/EBP binding site at +1 to +18. The mutation is a single base pair deletion from a triplet of thymine residues at +6 to +8. We show that the extent to which this mutation disrupts the binding of C/EBP to its binding site is less marked than the disruption caused by the +13 A→G mutation of FIX Norwich (1). This correlates with age-matched phenotypic data we have available for the patient reported here and that of FIX Norwich.